Managing Tasks Across the Work-Life Boundary: Opportunities, Challenges, and Directions - Williams, Alex; Iqbal, Shamsi; White, Ryen W.; Kiseleva, Julia (ACM Transactions on Computer-Human Interaction, 2023)
Task management tools allow people to record, track, and manage task-related information across their work and personal contexts. As work contexts have shifted amid the COVID-19 pandemic, it has become important to understand how these tools are continuing or failing to support peoples’ work-related and personal needs. In this paper, we examine and probe practices for managing task-related information across the work-life boundary. We report findings from an online survey deployed to 150 information workers during Summer 2019 (i.e., pre-pandemic) and 70 information workers at the same organization during Summer 2020 (i.e., mid-pandemic). Across both survey cohorts, we characterize these cross-boundary task management practices, exploring the central role that physical and digital tools play in managing task-related information that arises at inopportune times. We conclude with a discussion of the opportunities and challenges for future productivity tools that aid people in managing task-related information across their personal and work contexts.